Local Models in Register Classification by Timbre - Gero Szepannek; Uwe Ligges; Karsten Luebke; Nils Raabe; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
Investigating a data set containing different sounds of several instruments suggests that local modelling may be a promising approach to take into account different timbre characteristics of different instruments. For this reason, some basic ideas towards a local modelling are realized in this report yielding a framework for further studies.
Keywords: 519